Territorial Techniques for Controling the Peruvian Dry Forest: Catacaos Peasantries Facing the Expansion of Agribusiness During a Humanitarian Emergency - Burneo, María Luisa (Universidad del Rosario, 2020)
This paper analyzes the new land occupations of the common land located in the dry forest, over the northern Peruvian coast, in the context of forced displacement due to extreme climatic events and severe flooding. Peruvian peasant communities in the area go back to the sixteenth century, having customary rights over thousands of acres. However, over the last decade, agribusinesses have expanded their industry over communal land, creating new conflicts. Through ethnographic fieldwork, observations, and in-depth interviews between the years 2013 and 2018, this paper analyzes the case study of the peasant community of Catacaos. It presents the different territorial techniques used by the agribusiness for taking control over common lands, as well as emergent new narratives amongst local families looking to legitimize negotiations with private actors, showing the progressive loss of control over common lands and communal territory.